2021
DOI: 10.1002/ptr.7277
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Persian medicine herbal formulations (capsules and decoction) compared to standard care in patients with COVID‐19, a multicenter open‐labeled, randomized, controlled clinical trial

Abstract: Persian medicine has recommended clinical experiences and proper herbal remedies for prevention and treatment of microbial infections and respiratory diseases. An open-label, randomized, controlled, multicenter trial was conducted at five hospitals in Tehran and Isfahan provinces of Iran on 358 hospitalized adult patients. A total of 174 patients received standard care and 184 received herbal remedies (polyherbal decoction every 8 hr and two herbal capsules every 12 hr) plus standard care for 7 days. The prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 72 publications
0
37
0
2
Order By: Relevance
“…Several herbal/traditional medicines have been investigated for the treatment of mild and severe/critical COVID-19. They come from countries with well-known traditional medicine such as China (Xia et al, 2021;Xiao et al, 2020;Xu et al, 2021;Zhou et al, 2021), India (Devpura et al, 2021;Natarajan et al, 2021;Srivastava et al, 2021), and Iran (Karimi et al, 2021;Valizadeh et al, 2020). These studies showed that herbal medicines could Antitussive treatment 0 (0.0) 4 (12.5) .050…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several herbal/traditional medicines have been investigated for the treatment of mild and severe/critical COVID-19. They come from countries with well-known traditional medicine such as China (Xia et al, 2021;Xiao et al, 2020;Xu et al, 2021;Zhou et al, 2021), India (Devpura et al, 2021;Natarajan et al, 2021;Srivastava et al, 2021), and Iran (Karimi et al, 2021;Valizadeh et al, 2020). These studies showed that herbal medicines could Antitussive treatment 0 (0.0) 4 (12.5) .050…”
Section: Discussionmentioning
confidence: 99%
“…Several herbal/traditional medicines have been investigated for the treatment of mild and severe/critical COVID‐19. They come from countries with well‐known traditional medicine such as China (Xia et al, 2021 ; Xiao et al, 2020 ; Xu et al, 2021 ; Zhang et al, 2021 ; Zhou et al, 2021 ), India (Devpura et al, 2021 ; Natarajan et al, 2021 ; Srivastava et al, 2021 ), and Iran (Karimi et al, 2021 ; Valizadeh et al, 2020 ). These studies showed that herbal medicines could reduce SARS‐CoV‐2 viral load, hospital length of stay, time to symptom resolution in mild COVID‐19 patients, and mortality rate in patients with severe/critical COVID‐19, when compared with placebo.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement of the clinical symptoms was also mentioned in another RCT that investigated the effect of Persian medicine herbal formulations on patients with COVID-19 [17] . Patients in the mentioned study also reported significant improvement in fatigue, cough, myalgia, headache as well as fever, GI symptoms, vertigo, and chest pain as well as significantly shortened average length of hospital stay.…”
Section: Discussionmentioning
confidence: 90%
“…Traditional Persian medicine (TPM) has recommended potential functional foods candidates to manage COVID‐19. A clinical study demonstrated that Persian medicine herbal formulations (capsules and decoction) plus routine care significantly decreased duration of hospitalization, accelerated clinical improvement and decreased symptoms in the treatment group compared with standard‐care group (Karimi et al, 2021 ).…”
Section: Traditional Medicinementioning
confidence: 99%